Distribution of bacteriophages in food and environment samples - Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; Thung, Tze Young; New, Chia Yeung; Tang, John Yew Huat; Basri, Dayang Fredalina; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Foodborne pathogens have become a constant threat to the consumer and food industry. Reduce efficacy of antibiotics with emergence of resistant bacteria has limited the opportunities for controlling pathogenic bacteria in food commodities and treating foodborne infections. Bacteriophages can be a promising alternative for alleviate the risk of transmitting pathogenic bacteria via food commodities. Therefore, this research was conducted to find distribution of bacteriophages in diverse niches in order to identify suitable sources for isolating bacteriophages to use controlling foodborne pathogens. Firstly bacterial strains were screened for lysogenic and selected suitable host bacterial strains were used for isolating and determining bacteriophage titer in fresh raw food and environmental samples. Eighteen different lytic bacteriophages effective against Campylobacter, S. aureus, L. monocytogenes and E. coli were isolated from this study. Bacteriophages titer was determined within range of 102 to 1010 PFU/mL and bacteriophages were most frequently isolated from chicken (60%) samples. The isolated bacteriophages could be potential candidates for controlling foodborne diseases.